Stress and quality of life in pre-academic course students: Longitudinal study (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Stress is a physiological and psychological response to an unusual situation that requires the adaptation of the individual. Students who are preparing for selection test for admission to college are subjected to many stressful situations. They are exposed to the test itself stressors in addition to the internal and external. This study intended to verify that the simple passage of time and the proximity of the exam alter the condition of stress and quality of life of students. Subjects for phase one were 71 students from high school, and 12 other subjects participated in phase two and three. They answered the Sociodemographic Questionnaire, Stress Symptom Inventory and Quality of Life Inventory. The sample presented stress, psychological symptoms and low quality of life scores at the three different moments indicating that the permanence of stressors can be detrimental to the performance and quality of life.
Keywords: admission exam; stress; quality of life; longitudinal study